How do football managers describe their theory of change when joining a new club and to what extent do these approaches reflect best practices in the management literature? - Turner, Barry (2012)
This Management Project is designed to assess and evaluate how Football Managers, when joining a new club, describe their approaches to change and to what extent these approaches reflect best practice within the academic literature. The project will consist of a literature review which will discuss change from three different approaches: the planned approach, emergent approach and contingency approach. Within the literature review I will identify three frameworks which will be predominantly used when assessing the synergies between the approaches of the football manager compared with that of the academic literature. My research will consist of a number of semi structured interviews of past and present managers who have managed at a professional level. I will analyse these interviews using a process called Thematic Analysis. This will involve identifying key themes that are consistent across all interviews. I will provide a brief commentary on the relevance of the theme within the football environment and illustrate by using quotations from my research. The research will allow me to develop a discussion piece identifying any similarities or differences that have emerged from my assessment of the literature review. Within my discussion I will analyse how the managers describe their approach to change and compare this to the academic literature. I will predominantly use three key academic frameworks. These are Kotter (1996) Eight Stage Process, Dunphy & Stace (1993) contingency model and Watkins (2009) Stars model. In addition I will provide some general assessment of the managers’ approaches that demonstrate similar aspects to other structures and approaches discussed within my literature review. In addition I will highlight any limitations that I feel could be addressed to allow this project to offer a greater insight. Finally, I will conclude by offering my opinion on the question I asked myself which is the title of my project. I will identify any key learning points that have resonated with me and discuss thoughts on future research to develop this subject further.